2019
DOI: 10.1088/1361-6439/ab4527
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication strategy for an efficient lead zirconate titanate based piezoelectric micromachined ultrasound transducer

Abstract: This paper presents the design and fabrication strategy of a lead zirconate titanate (PZT)based piezoelectric micromachined ultrasound transducers (pMUT) with the objective of maximizing its performance. Choosing the most suitable thickness of the PZT layer, the radius of the top electrode, and the effect of the residual stress on the resonance frequency of a pMUT are investigated by finite element method (FEM) simulation and analytical equations. Three different architectures of pMUTs are presented: (i) a pMU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 42 publications
(50 reference statements)
1
11
0
Order By: Relevance
“…A similar tuning in resonant frequency due to change in strain has been reported in doubly clamped membranes, 44 beams, and PMUTs. 45,46 The resonant mode at 169.1 kHz is confirmed to be fundamental mode by mapping the mode shape (Figure S3). The dynamic response of D3 before (b 2 = 0.1006 and b 3 = 0.0180) and after annealing is shown in Figure 5b,c, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…A similar tuning in resonant frequency due to change in strain has been reported in doubly clamped membranes, 44 beams, and PMUTs. 45,46 The resonant mode at 169.1 kHz is confirmed to be fundamental mode by mapping the mode shape (Figure S3). The dynamic response of D3 before (b 2 = 0.1006 and b 3 = 0.0180) and after annealing is shown in Figure 5b,c, respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 89%
“…Transmission sensitivity is related to the output acoustic power per unit of input electrical power. It has been previously demonstrated that in order to have sufficient output acoustic power, the lateral dimension of the pMUT membrane should be equal to or bigger than half of the transmitted wavelength [16]. Therefore, based on the desired working frequency, lateral dimensions and the thickness of the membrane are optimized.…”
Section: Methodsmentioning
confidence: 99%
“…The capacitance of an element together with the parasitic resistors form a low pass filter with a bandwidth of 1/2RC. If the resonance frequency of the transducer is higher than this value, most of the input electrical power is consumed to charge and discharge the capacitor [16]. Hence, for the high frequency pMUTs an additional polyimide dielectric layer is introduced on top of the PZT layer, which works as an insulating layer, to reduce the parasitic capacitance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations